Impact of Neonatal Intensive Care Bed Configuration on Rates of Late-Onset Bacterial Sepsis and Methicillin-Resistant Staphylococcus aureus Colonization. (25th June 2015) - Julian, Samuel; Burnham, Carey-Ann D.; Sellenriek, Patricia; Shannon, William D.; Hamvas, Aaron; Tarr, Phillip I.; Warner, Barbara B.
Abstract : BACKGROUND: Infections cause morbidity and mortality in neonatal intensive care units (NICUs). The association between nursery design and nosocomial infections is unclear. OBJECTIVE: To determine whether rates of colonization by methicillin-resistant Staphylococcus aureus (MRSA), late-onset sepsis, and mortality are reduced in single-patient rooms. DESIGN: Retrospective cohort study. SETTING: NICU in a tertiary referral center. METHODS: Our NICU is organized into single-patient and open-unit rooms. Clinical data sets including bed location and microbiology results were examined over 29 months. Differences in outcomes between bed configurations were determined by χ 2 and Cox regression. PATIENTS: All NICU patients. RESULTS: Among 1, 823 patients representing 55, 166 patient-days, single-patient and open-unit models had similar incidences of MRSA colonization and MRSA colonization-free survival times. Average daily census was associated with MRSA colonization rates only in single-patient rooms (hazard ratio, 1.31; P=. 039), whereas hand hygiene compliance on room entry and exit was associated with lower colonization rates independent of bed configuration (hazard ratios, 0.834 and 0.719 per 1% higher compliance, respectively). Late-onset sepsis rates were similar in single-patient and open-unit models as were sepsis-free survival and the combined outcome of sepsis or death. After controlling for demographic, clinical, and unit-based variables, multivariate Cox regression demonstrated that bed configuration had no effect on MRSA colonization, late-onset sepsis, or mortality. CONCLUSIONS: MRSA colonization rate was impacted by hand hygiene compliance, regardless of room configuration, whereas average daily census affected only infants in single-patient rooms. Single-patient rooms did not reduce the rates of MRSA colonization, late-onset sepsis, or death. Infect Control Hosp Epidemiol 2015;36(10):1173–1182